Unraveling the gut microbiota–SCFAs–cathepsin C pathway in preeclampsia: a novel therapeutic target - Lu, Fan; Lei, Houkang; Xiao, Xiang; Yu, Luzhu (Frontiers in Immunology, 2025)
IntroductionPreeclampsia (PE) is a severe obstetric syndrome linked to impaired maternal-fetal immune tolerance, placental insufficiency, and systemic inflammatory activation. Emerging studies suggest that gut microbiota and its metabolites, especially short-chain fatty acids (SCFAs), play a pivotal role in the pathogenesis of PE. However, the precise molecular mechanisms through which SCFAs influence maternal-fetal immune interactions remain poorly understood.MethodsThis study combined clinical data and experimental models to explore the role of SCFAs in regulating cathepsin C expression, a key protease involved in immune modulation, and its impact on immune disturbances in PE. We analyzed the gut microbiota composition and serum SCFA levels in PE patients, and used an L-NAME-induced rat model of PE to assess the effects of SCFA supplementation. Additionally, forced cathepsin C overexpression in rats was performed to establish causality.ResultsOur findings revealed significant gut microbiota alterations in PE patients, with a reduction in SCFA-producing bacteria and an increase in inflammatory microbes. Clinically, SCFA levels were inversely correlated with cathepsin C expression, which was associated with hypertension and proteinuria. In rats, SCFA supplementation significantly reduced cathepsin C levels and alleviated PE symptoms, including hypertension, proteinuria, and fetal growth restriction. Furthermore, overexpression of cathepsin C negated the beneficial effects of SCFAs, exacerbating PE progression. Mechanistically, SCFAs modulated macrophage polarization by inhibiting cathepsin C, promoting the shift to an anti-inflammatory M2 phenotype.DiscussionThis study elucidates the "gut microbiota–SCFAs–cathepsin C–macrophage polarization" pathway as a crucial mechanism in the development of PE. SCFAs promote immune tolerance at the maternal-fetal interface by downregulating cathepsin C and driving M2 macrophage polarization. These findings offer new insights into potential therapeutic strategies for PE, including interventions aimed at modulating the gut microbiota to prevent or mitigate the disease.